Development and validation of a high-performance liquid chromatography-fluorescence detection method for the accurate quantification of colistin in human plasma - Chepyala, Divyabharathi; Tsai, I-Lin; Sun, Hsin-Yun; Lin, Shu-Wen; Kuo, Ching-Hua (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2015)
•A HPLC-FLD method was developed for colistin quantification in human plasma.•In-SPE derivatization method was applied for plasma sample preparation.•The developed method was applied to patient plasma samples for TDM. Recently, colistin has become one of the most important drugs for treating infections caused by multidrug-resistant Gram-negative bacteria. Therapeutic drug monitoring is recommended to ensure the safety and efficacy of colistin and to improve clinical outcomes. This study developed an accurate and sensitive high-performance liquid chromatography-fluorescence detection (HPLC-FLD) method for the quantification of colistin in human plasma. The sample preparation included protein precipitation using trichloroacetic acid (TCA) and methanol, followed by in-solid phase extraction (In-SPE) derivatization with 9-fluorenylmethyl chloroformate (FMOC-Cl). A Poroshell 120 EC-C18 2.1×100mm (2.7μm) column was used in the HPLC method with a mobile phase composed of acetonitrile (ACN), tetrahydrofuran (THF), and deionized (DI) water (82%, 2%, 16% (v/v), respectively). Polymyxin B1 was used as the internal standard. The total analysis time was 22min under optimal separation conditions. The HPLC-FLD method was validated over a therapeutic range of 0.3–6.0μgmL−1. The intra-day and inter-day precisions for colistin A and colistin B were below 9.9% and 4.5% relative standard deviations, respectively. The accuracy test results were between 100.2 and 118.4%. The extraction recoveries were between 81.6 and 94.1%. The method was linear over the test range, with a 0.9991 coefficient of determination. The limit of detection was 0.1μgmL−1. The validated HPLC-FLD method was successfully applied to quantify the colistin concentrations in 2 patient samples for therapeutic drug monitoring.